SYNTHESIS AND CHARACTERIZATION OF HYBRID PEROVSKITE (RNH3)2SNBR4 WITH SOME AMINES AND (PEA)2SNBRXI4-X - Anasha, Selvi
2D hybrid perovskite is one of the structural materials that has been widely developed and applied as a photodetector, solar cell and LED (Light Emitting Diode) material. A 2D hybrid perovskite with general formula A2MX4 is formed from organic cations (A+) and inorganic structures [MX4]2- which form an octahedral layer. The organic cation that is usually used is the ammonium ion while the inorganic structure usually uses two-valent metal element such lead (Pb). Pb-based perovskite has good electronic properties but has a high toxicity value that can damage health and environment. Therefore, lead-free perovskite was developed by replacing Pb with other metals which have Pb-like properties and low toxicity levels. One of the alternative metal elements to replace Pb is tin (Sn). In this research, synthesis of Sn-based hybrid perovskite compounds with some aliphatic amines (butylamine, amylamine, and hexylamine) and aromatic amines (phenethylamine) has been carried out. In addition, a synthesis of mixed halides (PEA)2SnBrxI4-x was also carried out. The synthesis was carried out by direct reaction of the reactants in the form of SnO, HBr/HI, H3PO2 and amine compounds at 90oC. The products was characterized using Atomic Absorption Spectroscopy (AAS), CHN Elemental Analyzer, argentometric titration, Scanning Electron Microscopy–Energy Dispersive X-ray (SEM-EDX), Powder X-Ray Diffraction (PXRD), Thermogravimetric Analysis (TGA) and photoluminescence (PL) spectroscopy. Based on the characterization of elemental content, the products molecular formulas are (BA)2SnBr4.HBr, (AA)2SnBr4.HBr, (HA)2SnBr4.1,5HBr, (PEA)2SnBr4.0,5HBr and (PEA)2SnBr0.75I3.25.HI with 54% to 80% yield. Perovskite with only Br halide is shaped like a thin layer which is yellow at room and green under UV light while perovskite with Br-I halide is shaped like a thin layer of reddish brown at room and red when under UV light. Based on the processing of diffractogram using the Bragg equation, the d-spacing value is obtained which is proportional to the elongation of the amine chain. The hybrid compound (RNH3)2SnBr4.xHBr with the cation butylammonium (BA), amylammonium (AA), hexylammonium (HA) and phenethylammonium (PEA) had the emission peaks were at 470, 472, 475 and 494 nm. The mixed halide compound (PEA)2SnBr0,75I3,25.HI has emission peaks at 595 nm. The addition of iodide ions in the mixture causes the emission to shift at a longer wavelength (red shift.) and increases d-spacing . In addition to experiments, computational studies were also carried out to know the stability of the material in terms of formation energy. Computational simulations were performed using Quantum Espresso and the input structure was arranged with a layer inorganic SnBr periodic system. The formation energies of (MA)2SnBr4, (BA)2SnBr4 and (PEA)2SnBr4 obtained are -2.0274 eV, -2.0571 eV and -2.3787 eV. Based on computational studies, the longer amines chain can increase structure stability of hybrid perovskite